Contextual Meaning Analysis in the Novel Kata by Rintik Sedu: A Semantic Study - Lidia Kristiani Situmorang; Pitri Ayuningsih; Firmansyah, Dodi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to analyze the contextual meaning in the novel Kata by Rintik Sedu using a semantic approach. Semantics studies the meaning of words, phrases, or sentences in language, both lexically and contextually. In literary works, language not only conveys messages explicitly but also through implicit meanings that are influenced by certain contexts. The novel Kata utilizes diction and situations to express deep meanings, especially those related to emotional experiences and interpersonal relationships between characters. The research method used is qualitative descriptive, with a focus on identifying and analyzing words, phrases, or sentences that contain contextual meanings in the novel. The results of the analysis show that the meanings in this novel are greatly influenced by the situational context, which allows readers to understand the meaning more deeply. This study contributes to the study of semantics and Indonesian literature, and enriches the understanding of how meaning is constructed in literary works through the context of its use.